Evaluation of Photoneutron Dose in the Medical Linear Accelerators by Manufacturer - Yang, Jeong-Mo; HwanLim, Cheong-; Yang, Oh-Nam (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The irradiation head of high-energy linear accelerator consists mainly of lead (82-Pb) or tungsten (74-W) characterized with a high atomic number. According to Report 79 of the National Council on Radiation Protection Measurement (NCRP) in the USA it is reported that there is a generation of photoneutrons through interaction with photons. The purpose of this study was to identify the amount of photoneutrons caused by changes in the field of irradiation under the same conditions, and to investigate the effects of photoneutrons on the interior space of the radiation therapy room using the radiotherapy equipment of Varian and Elekta. Methods/Statistical analysis: In this study, Varian Clinac iX and Elekta Versa HD Apex were used, and an optically stimulated luminescence dosimeter (OSLD) and reader Auto200 were used for determining the dose evaluation. The photoneutron measurement was noted at 10MV energy at 200MU, dose rate 300MU / min, and the irradiation field was measured by a dosimeter located at a predetermined point while adjusting the irradiation field to 10 × 10 ㎠, 20 × 20 ㎠, 30 × 30 ㎠. Findings: As a result of the measurement of photoneutrons by position according to the change of field, the field was increased proportionally as the field was determined to be wider in this case, The amount of photoneutrons in the center of the radiation therapy increased by 18% at 20 × 20 ㎠ and 35% at 30 × 30 ㎠, when the irradiation field was 10 × 10 ㎠. As a result of measurement of photoneutrons by location according to the manufacturer’s equipment, it was found that the amount of photoneutrons increased more rapidly in Elekta than in Varian, as the field of radiation therapy increased based on the central dose of radiation therapy. Improvements/Applications: Due to the structural characteristics of the linear accelerator, it is difficult to fundamentally block the generation of neutrons. However, since neutrons may have a potential effect on the outbreak of cancers in the surrounding organs, it is necessary to find ways to measure and apply neutron generation for each condition, which is especially important when establishing treatment plans with proper awareness of radiation-related workers in order to minimize neutron outbreaks